2012
DOI: 10.1039/c2dt30151b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures of (aminopyridine)nickel complexes and their use for catalytic ethylene polymerization

Abstract: A series of α-aminopyridines in the form of (2,6-C(6)H(3)N)(R(1))(CHR(2)NR(3)R(4)) (R(1) = R(2) = H R(3) = H R(4) = (i)Pr (L1a), R(4) = (t)Bu (L1b), R(4) = Ph (L1c), R(4) = 2,6-Me(2)C(6)H(3) (L1d), R(4) = 2,6-(i)Pr(2)C(6)H(3) (L1e), R(1) = R(2) = H R(3) = R(4) = Et (L1f), R(1) = H R(2) = Me R(3) = H R(4) = (i)Pr (L2a), R(4) = Ph (L2c), R(4) = 2,6-Me(2)C(6)H(3) (L2d), R(4) = 2,6-(i)Pr(2)C(6)H(3) (L2e), R(1) = Me R(2) = H R(3) = H R(4) = 2,6-(i)Pr(2)C(6)H(3) (L3e)) and β-aminopyridines in the form of (2-C(6)H(4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This may be the result of the high concentration of ethylene on increasing the solvent volume. 96 The nickel catalysts with 2-benzimidazolylpyridine ( 142 ) or benzoxazolylpyridine ( 143 ) organic supports were preeminently active in the oligomerization of ethylene for C4 and C6 products. Benzoxazolylpyridine gave higher activity than its 2-benzimidazolylpyridine analogue with selectivity up to 99% for C4 and 76% for α-C4.…”
Section: Other Structures Related To Iminopyridine Mononuclear Ni Cat...mentioning
confidence: 99%
“…This may be the result of the high concentration of ethylene on increasing the solvent volume. 96 The nickel catalysts with 2-benzimidazolylpyridine ( 142 ) or benzoxazolylpyridine ( 143 ) organic supports were preeminently active in the oligomerization of ethylene for C4 and C6 products. Benzoxazolylpyridine gave higher activity than its 2-benzimidazolylpyridine analogue with selectivity up to 99% for C4 and 76% for α-C4.…”
Section: Other Structures Related To Iminopyridine Mononuclear Ni Cat...mentioning
confidence: 99%
“…Specifically, the two N atoms of contrasting basicities, separated by three C atoms, welcomes a litany of mono-and bidentate ligation to transition and heavy metals. Such diamines are commonly found in metal complexes that catalyze a number of organic transformations (Tai et al, 1986;Nam & Valentine, 1990;Nam et al, 1994;Hirao et al, 1996;Rispens et al, 1996;Lei & Chelamalla, 2013;Scholl et al, 2013), and their complexes have demonstrated promise as anticancer candidates (Dhar et al, 2005;Thyagarajan et al, 2006;Gupta et al, 2008;Zhu et al, 2008;Souza et al, 2009;Xu et al, 2009;Xue et al, 2010;Da Silveira et al, 2011;Panja et al, 2011;Kumar et al, 2012) and polymerization catalysts (Tshuva et al, 2001;Lee et al, 2006;Lin, Yu et al, 2012;Shaikh et al, 2012), and even have potential in fuel cells (Tahsini et al, 2012;Das et al, 2013). Surprisingly, very little is understood regarding the specific medicinal and synthetic potential of N-[2-(pyridin-2-yl)ethyl]-substituted sulfonamides or their corresponding metal complexes, and it is imperative to synthesize a complex library of these molecules in order fully to explore and exploit their potential in these arenas.…”
Section: Introductionmentioning
confidence: 99%
“…A similar example is apparent from careful analysis of a recent report on the Ni(II)-bromide complex of the N-substituted 2- (2-pyridyl)ethylamine bidentate ligand having a hindered diethyl group, which offers a wide bite angle (97°) and stabilizes the four-coordinate tetrahedral geometry. 25 The Ni−N am bond is longer than Ni−N py as expected; this is due to the bulky biphenyl group on the amine nitrogen, which makes N am a weaker σ-donor. The coordination geometry and bond parameters of Ni(II) in 1a−c are comparable to those of related structures.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
“…The widening of the angle in the present case is due to the combined effect of both the ethyl spacer and sterically hindered biphenyl group. A similar example is apparent from careful analysis of a recent report on the Ni­(II)-bromide complex of the N-substituted 2-(2-pyridyl)­ethylamine bidentate ligand having a hindered diethyl group, which offers a wide bite angle (97°) and stabilizes the four-coordinate tetrahedral geometry …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation